The greediest of Rajahs and the whitest of clouds Ang pinakasakim na Raha at ang pinakamaputing ulap - Ibardolaza, Honoel; Vallesteros, Brian (Quezon City Adarna House, 2004)
A story of a rajah whose greed leads to his failure
Rekomendado sa mga batang edad 4-6.
First Prize Short Story for Children 2003: Don Carlos Palanca Memorial Awards for Literature .